106 Lack of Insurance Leads to Increased Mortality After Craniotomy. (1st April 2022) - Cua, Santino; Shah, Varun; Dornbos, David L.; Hoang, Nguyen; Kreatsoulas, Daniel C.; Eaton, Ryan; Rodgers, Brandon; Pezzutti, Dante; Duenas, Helen; Nimjee, Shahid M.
Abstract : INTRODUCTION: Socioeconomic status directly impacts outcomes in healthcare. Prior studies have demonstrated the impact of insurance type and status on postoperative outcomes in subspecialty populations, including peripheral tumor and spine. There is a paucity of literature addressing the impact of socioeconomic status on neurosurgical outcomes. This study seeks to investigate socioeconomic factors, namely insurance status, and their impact on adverse events and outcomes in patients undergoing a craniotomy. METHODS: A single center, retrospective cohort study was conducted on neurosurgical patients undergoing a craniotomy from 2013-2018. Preoperative demographics, comorbidities, surgical variables, postoperative adverse events, and mortality within 90-days of surgery were collected. Socioeconomic variables include insurance, employment, and disability statuses. Statistical analysis utilizing the Mann-Whitney U test, independent sample t-test and multivariate logistic regression analyses with an alpha of 0.05 were used to compare differences in demographic baseline, adverse event rates and outcomes between patients with and without insurance. RESULTS: 2445 patients who underwent a craniotomy were included in the analysis with 5.4% being uninsured. Baseline demographic analysis found an increased prevalence of unemployment among uninsured patients (38.3% v 50.0%, p = 0.007). Uninsured patients were significantly younger (p < 0.001) and had higher prevalence of non-opioid substance use (p = 0.027). Adverse events were higher in uninsured patients, including higher rate of acute respiratory insufficiency (p=0.002), delirium (p=0.039) and non-surgical site related infections (p=0.001) compared to insured patients. After controlling for confounders (including age, sex, employment status, disability, substance use, tobacco use, hyperlipidemia, supratentorial patholoy, surgical time), uninsured patients had higher odds of 90-day mortality (OR 2.393, 95% CI 1.321 – 4.334, p = 0.004). CONCLUSION: Lower socioeconomic status negatively impact postoperative outcomes in patients undergoing craniotomy. Namely, uninsured patients experienced significantly increased 90-day mortality following craniotomy. It is imperative that insurance status be considered in developing comprehensive treatment plans for each patient in order to minimize the risk of disparate outcomes after undergoing a craniotomy.